242 HEALTH CARE DISPARITIES IN AFRICAN AMERICAN PATIENTS WITH CHRONIC KIDNEY DISEASE. (1st January 2006) - Wofford, P.; Britton, L.; Valentine, K.; Schmidt, D.; Flessner, M.
Abstract : Background: Disparities in the treatment of asymptomatic diseases such as chronic kidney disease (CKD) may result in more rapid progression toward end-stage renal disease. Our hypothesis is that elimination of these disparities will slow the progression of this disease. Objective: The purpose of this study is to investigate the disparities in asymptomatic CKD patients as a first step in the development of interventions to eliminate HCD in an African American cohort. Methods: We prospectively enrolled 115 patients from the University Renal Clinic who have a MDRD-estimated glomerular filtration rate (GFR) between 7 and 75 mL/min/1.7 m≤. All patients completed a SF-36 quality of life survey and a locus of control survey, in which the patient defines who has responsibility for his health. These data plus level of education, income, and insurance status were correlated with the following factors: age, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), serum creatinine (SCr), MDRD-GFR, and compliance with appointments and number of medications. Results: The patient characteristics (n = 115) were 62% female, 38% male, 21% without insurance, 23% with Medicaid, 38% Medicare, and 15% other. Eighty-one percent had an annual family income < 20, 000; 40% had less than a high school education; 63% were disabled. Patient locus of control was found to be primarily with physicians and nurses rather than self. Lower GFR was correlated with less compliance with follow-up, more medications, poor sex life, lower income, less schooling, unemployment, the patient's perceived burden of disease, and anxiety and feeling of isolation. There were few consistent correlations with blood pressure. Conclusion: From this cross-sectional analysis of African American CKD patients, we conclude that lower GFR and quality of life correlate with older age, lower socioeconomic status, lack of compliance with follow-up, and beliefs that transfer responsibility for health to providers.